2010
DOI: 10.1007/s00266-010-9544-4
|View full text |Cite
|
Sign up to set email alerts
|

Experience Using the Thoracodorsal Artery Perforator Flap in Axillary Hidradentitis Suppurativa Cases

Abstract: Hidradenitis suppurativa is a chronic and recurrent inflammatory disease of the apocrine glands characterized by recurrent abscesses, draining sinus tracts, and scarring that can be located in the groin, axilla, perineal, and perianal areas and less frequently in the scalp area. The chronic and relapsing nature of hidradenitis suppurativa leads to physical and psychological damage because it frequently causes disabling pain, diminished range of motion, and social isolation. Surgical removal of all apocrine gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
1
14
0
3
Order By: Relevance
“…In addition to these factors, the longer hospital stays as compared with other reconstruction strategies and low scores on range of motion and appearance most likely contributed to the fact that we found FCF to be associated with the lowest median total patient-reported score (14 out of 20). Nevertheless, FCF with the Limberg transposition flap, 16 thoracodorsal artery perforator flap, 17 thin circumflex scapular artery perforator flap, 18 scapular island flap, 19 posterior arm fasciocutaneous flap, 20 and lattisimus dorsi flap 21 is increasingly being used after wide excision. Studies will be required to evaluate whether certain techniques are associated with improved outcomes as compared to the use of other flaps.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these factors, the longer hospital stays as compared with other reconstruction strategies and low scores on range of motion and appearance most likely contributed to the fact that we found FCF to be associated with the lowest median total patient-reported score (14 out of 20). Nevertheless, FCF with the Limberg transposition flap, 16 thoracodorsal artery perforator flap, 17 thin circumflex scapular artery perforator flap, 18 scapular island flap, 19 posterior arm fasciocutaneous flap, 20 and lattisimus dorsi flap 21 is increasingly being used after wide excision. Studies will be required to evaluate whether certain techniques are associated with improved outcomes as compared to the use of other flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary healing is less desirable as it may cause contractures and subsequent limitation in the arm's range of movement leading to stiffening of the shoulders [15]. Commonly cited primary closure methods for axillary HS include the use of direct closure, split thickness skin graft (STSG), fasciocutaneous flap, musculocutaneous flap, parascapular flap, thoracodorsal artery perforator flap (TDAP) and posterior-arm flap [612161718]. A further innovative method for reconstruction has been introduced over the last few years with the addition of the inner-arm flap [19].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the thoracodorsal artery perforator (TDAP) flap was demonstrated in several studies and it was shown able to maintain the diamond shape of the axilla with minimal donor site morbidity [12]. TDAP flaps have also been shown to be superior in postoperative arm abduction compared to other reconstructive procedures [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In extensive anogenital AI defect, closure is performed in many departments, but contour after skin grafting often is unsatisfactory. [108]…”
Section: Introductionmentioning
confidence: 99%